Development of Russian Next-generation Ablative Pulsed Plasma Thrusters. (2017) - Antropov, N.N.; Bogatyy, A.V.; Boykachev, V.N.; Dyakonov, G.A.; Lyubinskaya, N.V.; Popov, G.A.; Semenikhin, S.A.; Tyutin, V.K.; Yakovlev, V.N.
Abstract: The development of ablative pulsed plasma thrusters (APPT) continues at RIAME MAI. In 2014 one of them, APPT-45-2, was mounted on board the small spacecraft MKA-FKI PN2 developed by the S.A. Lavochkin Scientific and Production Association. Now in cooperation with the Scientific Technical Innovation Center "TECHCOM" the electric propulsion system (EPS) APPT-250 of the next generation is being developed, that is intended for the orbit maintanance of the constellation of small communication satellites. Power consumption of EPS is from 60 to 120 W, the total thrust impulse is 15.6 kNs. APPT-250 differs from the earlier APPT-based propulsion systems by substantially lower mass. A digital power processing unit (PPU), developed by "TECHCOM", and power capacitors with high specific energy intensity are used for the first time.